Implementasi RFID sebagai keamanan koleksi di Perpustakaan UIN Sayyid Ali Rahmatullah Tulungagung - Rahayu, Septi; Handayani, Nurul Setyawati (Faculty of Communication, Padjadjaran University, 2024)
The security of collections is critically important for safeguarding college libraries. One of the security measures implemented is the use of RFID (Radio Frequency Identification) systems. This study aims to examine the application of RFID technology for collection security and to identify the challenges encountered in its implementation at the UIN Sayyid Ali Rahmatullah Tulungagung Library. The research employs a qualitative descriptive approach, systematically and accurately portraying the facts observed in the field. The informants include the head librarian and the coordinator of the ICT introduction and repository. Data collection methods consist of observation, interviews, and documentation. Data analysis techniques involve data reduction, presentation, and conclusion drawing. The findings reveal that the RFID system effectively enhances collection security at the UIN Sayyid Ali Rahmatullah Tulungagung Library. Security is achieved through stickers affixed to the back covers of books, making them less noticeable to users. Furthermore, RFID technology can detect books that have not been checked out by triggering an alarm when passing through the security gate. A significant challenge faced is the frequent downtime of the system network, which cannot be resolved immediately. This issue may disrupt borrowing transactions, leading to discrepancies in transaction data within the application. Such challenges can be mitigated by increasing the bandwidth to address the existing issues adequately.